2007
DOI: 10.1080/17446540601118301
|View full text |Cite
|
Sign up to set email alerts
|

Gold investment as an inflationary hedge: cointegration evidence with allowance for endogenous structural breaks

Abstract: This note tests for the presence of a stable long-run relationship between the monthly price of gold and inflation in the United States from 1945 to 2006 and from 1973 to 2006. Since both the price of gold and the consumer price index have been subject to structural change over time, a novel unit root testing procedure is employed which allows for the timing of significant breaks to be estimated, rather than assumed exogenous. After taking these endogenously determined structural breaks into account, a modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
89
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(97 citation statements)
references
References 29 publications
8
89
0
Order By: Relevance
“…These precious metals have advantages, because of their durability, and can act as a hedge towards inflation (Beckmann and Czudaj 2012;Dee et al 2013;Ghosh et al 2004;Tkacz 2007;Worthington and Pahlavani 2007). Hammoudeh et al (2010) even concluded that precious metals could also act as a hedge for exchange rates.…”
Section: Introductionmentioning
confidence: 99%
“…These precious metals have advantages, because of their durability, and can act as a hedge towards inflation (Beckmann and Czudaj 2012;Dee et al 2013;Ghosh et al 2004;Tkacz 2007;Worthington and Pahlavani 2007). Hammoudeh et al (2010) even concluded that precious metals could also act as a hedge for exchange rates.…”
Section: Introductionmentioning
confidence: 99%
“…In their framework, the timing of structural breaks is endogenously determined by applying the unit root testing procedure developed by Zivot and Andrews (1992) and thereafter a modified cointegration approach suggested by Saikkonen and Lütkepohl (2000a, 2000b, 2000c) is adopted. The results provide evidence in favor of a cointegrating relationship between the price of gold and inflation in both sample periods and thus, Worthington and Pahlavani (2007) conclude that a gold investment can serve as an effective inflationary hedge. Finally, have analyzed the short-run and long-run inflation hedging effectiveness of gold in the USA and Japan for a sample period ranging from January 1971 to January 2010 while using monthly data.…”
Section: Literature Reviewmentioning
confidence: 65%
“…Kolluri (1981), Moore (1990), Laurent (1994), Chappell and Dowd (1997), Mahdavi and Zhou (1997), Harmston (1998), Ghosh et al (2004, Levin and Wright (2006), Worthington and Pahlavani (2007) and examine the inflation hedge effectiveness of gold by focusing on the short-run and the long-run relationship between the general price level and the price for gold. It is worth mentioning that studies which focus on 'safe haven' aspects mostly adopt daily instead of monthly data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tully and Lucey (2007) conclude that the US dollar is the major determinant for gold returns. Capie et al (2005) evidence the hedging quality of gold against the dollar while Sherman (1982); Baker and Van-Tassel (1985); Kaufmann and Winters (1989); Sjaastad and Scacciavillani (1996); McCown and Zimmerman (2006); Worthington and Pahlavani (2007); Wang et al (2011);Beckmann and Czudaj (2013) adduce the inflation-hedging trait of gold. Kutan and Aksoy (2004) contrarily document that gold does not carry the inflation hedging quality in Turkey.…”
mentioning
confidence: 99%